Collaborative Governance Dalam Pengembangan Desa Wisata Waduk Penjalin Di Desa Winduaji Kecamatan Paguyangan Kabupaten Brebes - Ajis Setiawan; Chamid Sutikno (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
This study aims to determine the collaborative governance process in the development of tourist villages in Winduaji Village, Paguyangan District, Brebes Regency. The existence of village autonomy policies and laws regarding village development that are carried out independently can provide opportunities for village governments to carry out village development by utilizing potential resources they have to meet community needs in particular and in general. The purpose of the study was to find out (1) the collaborative governance process in the development of tourist villages in Winduaji Village which was able to obtain a form of achievement award in the field of tourism village development. This research was conducted using a qualitative method, with a descriptive approach. The informant selection technique used purposive sampling technique. The data analysis technique uses an interactive analysis model, while the data validity uses triangulation to obtain valid data. The results of the study show that in the collaborative governance process in the development of tourist villages in Winduaji Village, it shows that in the development of tourist villages each involved party has a role, starting from the government, the community, tourism awareness groups, the private sector so that they are able to create useful activities and provide benefits. positive impact on society in particular and in general. Keywords; Collaborative Governance, Tourism Village, Tourism Awareness Group.